Probing Cell‐Surface Interactions in Fungal Cell Walls by High‐Resolution 1H‐Detected Solid‐State NMR Spectroscopy. Issue 1 (10th November 2022) - Safeer, Adil; Kleijburg, Fleur; Bahri, Salima; Beriashvili, David; Veldhuizen, Edwin J. A.; van Neer, Jacq; Tegelaar, Martin; de Cock, Hans; Wösten, Han A. B.; Baldus, Marc
Abstract: Solid‐state NMR (ssNMR) spectroscopy facilitates the non‐destructive characterization of structurally heterogeneous biomolecules in their native setting, for example, comprising proteins, lipids and polysaccharides. Here we demonstrate the utility of high and ultra‐high field 1 H‐detected fast MAS ssNMR spectroscopy, which exhibits increased sensitivity and spectral resolution, to further elucidate the atomic‐level composition and structural arrangement of the cell wall of Schizophyllum commune, a mushroom‐forming fungus from the Basidiomycota phylum. These advancements allowed us to reveal that Cu(II) ions and the antifungal peptide Cathelicidin‐2 mainly bind to cell wall proteins at low concentrations while glucans are targeted at high metal ion concentrations. In addition, our data suggest the presence of polysaccharides containing N‐acetyl galactosamine (GalNAc) and proteins, including the hydrophobin proteins SC3, shedding more light on the molecular make‐up of cells wall as well as the positioning of the polypeptide layer. Obtaining such information may be of critical relevance for future research into fungi in material science and biomedical contexts. Abstract : How 1 H‐detected fast MAS ssNMR spectroscopy can be applied for in‐depth characterization of the Schizophyllum commune cell wall architecture and composition, as well as the elucidation of cell surface‐level interactions. The obtained results reveal the relative abundance and arrangement of the polysaccharide and polypeptide layers and their significance in the binding of ligands to the fungal cell wall.